Socialization of the Use of Meta AI to Improve the Quality of MSME Marketing Content and Increase Sales Quantity: Pengabdian - Basnendar Herry Prilosadoso; Dinesh Basti Farani; Rahmawati Yuliani; Priyono Sadjijo; Afen Prana Utama Sembiring (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Competition in the digital market requires Micro, Small, and Medium Enterprises (MSMEs) to consistently produce attractive, persuasive, and high-quality marketing content . MSMEs at the village and regional levels, such as community service partners in West Java, Central Java, East Java, and Medan (North Sumatra) , face major obstacles in the form of limited human resources and copywriting and design skills, which results in stagnant sales quantities. This community service research aims to address these gaps through Socialization and Hands-on Training on the Utilization of Generative Artificial Intelligence Technology (Meta AI) . The training program focuses on the practical application of Meta AI for brainstorming content ideas, drafting effective promotional narratives, and optimizing customer chatbot strategies . The implementation method involves (1) Focus Group Discussion (FGD) to map the specific needs of MSMEs in each location, (2) Intensive training for 10 days, and (3) Mentoring and practical evaluation for two months. Post-training evaluation results showed a dramatic increase in the variety and quality of digital marketing content produced, supported by an 18% increase in average sales volume for MSMEs actively implementing the AI ​​tools . This success confirms that easily accessible AI adoption is a crucial strategy for increasing the competitiveness of regional MSMEs and accelerating digital economic inclusion.